Evaluation of Cash Waqf Linked Sukuk as a Tool for Public Infrastructure Development - Maya Kirana (PAPUA: International Journal of Sharia Business Management, 2025)
This study evaluates the effectiveness of Cash Waqf Linked Sukuk (CWLS) as an innovative Islamic financial instrument to support public infrastructure development. The analysis explores how CWLS integrates the philanthropic spirit of waqf with the stability of sovereign sukuk to generate sustainable social and economic value. The study investigates governance frameworks, operational mechanisms, risk mitigation strategies, and the distribution of social returns to beneficiaries. It also examines the extent to which CWLS enhances financial inclusion by mobilizing small-scale contributions into productive, long-term infrastructure projects. Empirical evidence highlights CWLS’s potential to reduce government financing burdens, increase community participation, and strengthen the resilience of Islamic social finance. Despite its promising impact, the study identifies several challenges, including limited public awareness, regulatory constraints, and the need for stronger institutional collaboration. Overall, CWLS demonstrates significant potential as a complementary tool for financing essential public infrastructure in a socially responsible and Sharia-compliant manner.